Sex Differences in the Amygdala Resting State Connectome of Children with Autism Spectrum Disorder - Lee, Joshua K. (Biol Psychiatry Cogn Neurosci Neuroimaging, 2019)
BACKGROUND: Multifactorial liability models predict greater dissimilarity in the neural phenotype of autism spectrum disorder (ASD) in females than in males, while Gender Incoherence and Extreme Male Brain models predict attenuated sex differences in ASD. The amygdala is an informative target to explore these models because it is implicated in both the neurobiology of ASD and sex differences in typical development (TD). METHODS: We investigated amygdala resting-state functional connectivity in a cohort of 116 ASD (36 female) and 58 TD children (27 female) aged 2 to 7 years during natural sleep. First, multivariate distance matrix regression assessed global sex and diagnostic differences across the amygdala connectome. Second, univariate general linear models identified regions with mean connectivity differences. RESULTS: Multivariate distance matrix regression revealed greater differences between TD and ASD children in females than in males, consistent with multifactorial liability models, and attenuated sex differences in the left amygdala connectome of children with ASD in a pattern consistent with the Gender Incoherence model. Univariate analysis identified similar sex differences in dorsomedial and ventral prefrontal cortices, lingual gyrus, and the posterior cingulate cortex, but also that lower amygdala connectivity with superior temporal sulcus is observed across sexes. CONCLUSIONS: We provide evidence that ASD in males and females manifests differently in the brain compared to sex-matched controls at the time of diagnosis and prior to the influence of compensatory mechanisms, consistent with multifactorial liability models, and that ASD is associated with reduced sex differences in a pattern consistent with gender incoherence models.